THE PERCEPTION OF SPECIAL EDUCATION TEACHERS TOWARDS PUPILS WITH DOWN SYNDROME (Proceedings of International Conference on Special Education, 2019)
This study aimed to investigate the perception of special education teachers on the characteristics and problems of children with Down Syndrome. This study is a survey using a questionnaire which has 45 items administered to 50 teachers of special education. The study is adopting quantitative research concept. Data were analyzed using the Statistical Package for Social Sciences version 22.0 for descriptive window, which are to generate descriptive and inferential statistic. The finding have shown that learning a critical problem among children with Down Syndrome is a high level, exceeding the third quarter or 75 percent giving positive feedback. Overall, the finding clearly show that the positive feedback on the characteristics and problems of children with Down Syndrome. Also concluded that in order to teach children with Down Syndrome, a teacher needs to understand the characteristic and learning problems of students with Down syndrome before being able to improve the quality of special education services.